Opportunistic parasitoses among Egyptian hemodialysis patients in relation to CD4+ T-cell counts: a comparative study - Amany I. Shehata; Faika Hassanein; Rashad Abdul-Ghani (BioMed Central (BMC), 2019)
Background: Some reports are available on the prevalence of opportunistic parasitoses among hemodialysis (HD) patients, yet there is a paucity of data on the association of CD4+ T-cell counts with such infections. Therefore, this study aimed to determine the prevalence of intestinal parasites and Toxoplasma gondii in relation to CD4+ counts among HD patients in Alexandria, Egypt. Methods: A comparative cross-sectional study was conducted on 120 HD patients and 100 apparently healthy individuals between December 2014 and January 2016. Data and samples (stool and blood) were collected from the participants after obtaining their informed consent. Stool samples were examined for parasites after concentration and staining, EDTA-blood samples were used for CD4+ counting by flow cytometry, and sera were analyzed for anti-Toxoplasma IgM and IgG antibodies. Results: A significantly higher prevalence rate of intestinal parasitoses was found among HD patients compared to apparently healthy individuals (52.5% vs. 12.0%, respectively), with absence of helminths. Cryptosporidium species (32.5%), B. hominis(24.2%) and microsporidia (11.7%) were the most frequent parasites among HD patients, while B. hominis (13.0%), Cryptosporidium species (11.0%) and G. lamblia (4.0%) were the most frequent parasites among their counterparts. Statistically significant differences in parasite infection rates between patients and their counterparts were found for Cryptosporidium species, B. hominis and microsporidia. However, parasite species were not significantly associated with diarrhea. On the other hand, the overall T. gondii seroprevalence rate among HD patients was significantly higher than that among their counterparts (33.3% vs. 8%, respectively). HD patients with CD4+ counts < 200 cells/?l were twice more exposed to intestinal parasitoses compared to those with counts ?200 cells/?l, but the difference was not statistically significant. However, low CD4+ counts were significantly associated with higher rates of Cryptosporidium species, microsporidia and T. gondii. Conclusions: Intestinal parasitoses and T. gondii infection rates are significantly higher among Egyptian HD patients compared to apparently healthy individuals, with Cryptosporidium species, B. hominis, microsporidia and T. gondii being the most frequent parasites. CD4+ counts < 200 cells/?l are significantly associated with Cryptosporidium species, microsporidia and T. gondii among HD patients. Therefore, regular screening of HD patients for opportunistic parasites is recommended.